Briófitas do Parque Estadual Pedra Azul (PEPAZ), município de Domingos Martins, Espírito Santo, Brasil - Silva, Lorena Tereza da Penha (2011)
The Pedra Azul State Park (PEPAZ) is situated at the extreme South of Espírito Santo State, in Domingos Martins (20º23´32”-20º29´24”S and 40º00´25”-40º59´29”W), with a small portion of its territory inserted on Vargem Alta municipal district, with an altitudinal variation from 1.200 to 1.900m. The Park has as main vegetational formations the Montane and High Montane Ombrophyllous Forests, associated with other vegetation communities like rock associated vegetation, seasonal height forest, and riparian forest. The samplings were made every two months during the period between March 2009 and March 2010. The samples were stored at ALCB, HUFS and VIES herbaria. Seven hundred and seventy six samples were determined, resulting in a total of 233 taxa. Regarding the liverworts, 107 species were found, belonging to 22 families represented by 44 genera. For mosses, 126 species were registered, distributed in 36 families and 86 genera. Sixty five species are first occurrences for Espírito Santo state. Daltonia tenuifolia Mitt., Taxiphyllum scalpelifolium (Müll. Hal.) Broth., Meteorium pseudoteres W.R. Buck, and Tortula mucronifolia Schwägr are new occurrences for Brazil. Regarding the species geographic distribution in Brazil, 48,3% of them have broad distribution, occurring in more than 9 states. In the other hand, 37,2% of the species have moderated distribution, occurring in 5 to 9 states and just 14,5% fit the category of restrict distribution, occurring in up to 4 brazilian states. The ecological range, given by the variability of colonized substrates, was corticicolous-rupicolous-terricolous-epixilous-epiphyllous. The predominant bryocenological group was corticicolous with 60,7% of the species, of which 28,4% are exclusive, demonstrating that living tree trunks were the preferential substrate. Due to the richness of bryophytes within Pedra Azul State Park, it is imperative to implement and increase the scientific researches in the region. It is also necessary to make more floristic inventories, a basic tool extremely to obtain knowledge about the biodiversity.